Factors related to critical thinking disposition and critical thinking skills of undergraduate students at a Malaysian Public University - Ghadi, Ibrahim Nazem Mahmoud (2013)
The purpose of this study was to determine the Critical Thinking Dispositions (CTD) and Critical Thinking Skills (CTS) by Universiti Putra Malaysia (UPM) undergraduate students. Three objectives were stipulated, 1) to identify the CTD levels among undergraduate students from different majors of study (science-based and arts-based) versus, gender and academic year of study; 2) to identify the CTS levels among undergraduate students from different majors of study (science and arts-based) versus, gender and academic year of study;3) to identify the dominant CTD elements that may influence CTS. In this research, a quantitative survey method was employed using descriptive and inferential statistics such as t-test, and multiple-regression in analyzing the data. The t-test was employed to achieve the first and second objectives that aim to identify the CTD as well as CTS levels of university undergraduate students of different gender, year of study and major of study. While, to achieve the third objective multiple-regression was used to identify the influence of CTD on CTS. Critical thinking ability instrument was measured by the researcher in order to meet the requirements of the current study. The instrument was translated into bilingual mode (Bahasa Malaysia and English) to answer the critical thinking ability questions and items. Nine hundred and fifty one students from sixteen science-based and arts-based faculties in UPM responded to the survey. The results indicated that, the CTD elements were on an average while CTS for the independent factors (gender, year of study and academic major) were on a high level. The result further shows a significant difference between CTD according to gender as well as CTS according to first and fourth year of studies. However, no significance difference was shown between CTD level according to major (science and arts) and year (first and fourth) on one hand and CTS level according to gender and major (science and arts). Furthermore, the CTD elements that have influence on CTS are analyticity, truth seeking, selfconfidence and maturity. In conclusion, the study reveals an interdependent relationship between CTD and CTS with the CTD elements being on the average level while CTS elements were on a high level. These results spell the need to inculcate the idea of developing critical thinking ability in the minds of students. Specifically,the need to strengthen the curriculum in the area of critical thinking especially for the newly enrolled undergraduate students is necessary to strengthen their potentials both professionally and academically.